2013
DOI: 10.1007/s10143-013-0496-4
|View full text |Cite
|
Sign up to set email alerts
|

Transsphenoidal cyst cisternostomy with a keyhole dural opening for sellar arachnoid cysts: technical note

Abstract: A less invasive transsphenoidal approach with a keyhole dural opening for intrasellar arachnoid cysts is described. This approach was used to address seven sellar cystic lesions with suprasellar extension; they were six intrasellar arachnoid cysts (IACs) and one Rathke's cleft cyst (RCC). In all cases, preoperative MRI revealed cerebrospinal fluid (CSF) intensity on both T1- and T2-weighted images. On preoperative contrast-enhanced MRI, five of the six IACs manifested posterior displacement of the flattened pi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
25
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(26 citation statements)
references
References 22 publications
0
25
0
1
Order By: Relevance
“…As described by Elliot et al suprasellar ACs are characterized by a pure cystic lesion with no contrast enhancement and calcification with a typical CSF-like signal behavior, that is a hypointense T1-weighted signal and a hyperintense T2-weighted signal on the MRI images [18] . Complementary to this, MRI findings showing a cystic intrasellar lesion with suprasellar extension, a balloon-shape, regular, isoor slightly hyper-intense to CSF, molding but no invasion to cavernous sinus may suggest a diagnosis of IAC [8] , [11] . MRI findings were consistent with these features except the rim like contrast enhancement in our patient.…”
Section: Discussionmentioning
confidence: 74%
See 1 more Smart Citation
“…As described by Elliot et al suprasellar ACs are characterized by a pure cystic lesion with no contrast enhancement and calcification with a typical CSF-like signal behavior, that is a hypointense T1-weighted signal and a hyperintense T2-weighted signal on the MRI images [18] . Complementary to this, MRI findings showing a cystic intrasellar lesion with suprasellar extension, a balloon-shape, regular, isoor slightly hyper-intense to CSF, molding but no invasion to cavernous sinus may suggest a diagnosis of IAC [8] , [11] . MRI findings were consistent with these features except the rim like contrast enhancement in our patient.…”
Section: Discussionmentioning
confidence: 74%
“…Intracranial arachnoid cysts (AC) are benign lesions of the arachnoid, forming nearly 1% of all intracranial space-occupying lesions [1] . Compared to other cystic lesions of the sellar region namely the cystic adenomas, craniopharyngiomas and Rathke's cleft cysts, they are rarely seen in this localization with few reports available in the English literature [2] , [3] , [4] , [5] , [6] , [7] , [8] , [9] , [10] , [11] , [12] , [13] , [14] . ACs are most commonly found in the Sylvian fissure followed by the cerebellopontine angle, the supracollicular area and the vermian area.…”
Section: Introductionmentioning
confidence: 90%
“…None of studies in the literature reported the occurrence of postoperative chemical meningitis after craniotomy of Rathke's cleft cysts, even in suprasellar Rathke's cases involving partial cyst wall removal [ 17 , 18 ]. Oyama et al published the method of transsphenoidal cyst cisternostomy with a keyhole dural opening [ 12 ]. The microscopical approach and the extended transsphenoidal approach were used.…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, most authors claim that currently the best method of proceeding is the use of endoscopic techniques. These techniques combine the high effectiveness, attributed to microsurgical procedures, with low invasiveness, specific for the implantation of valvular systems [33]. Approaches for accessing the suprasellar region in endoscopic techniques are: transfrontal/transcallosal and endonasal/ transsphenoidal.…”
Section: Emotional Disorders and Mental Retardationmentioning
confidence: 99%